2016
DOI: 10.1038/ncomms12026
|View full text |Cite
|
Sign up to set email alerts
|

A combined cryo-EM and molecular dynamics approach reveals the mechanism of ErmBL-mediated translation arrest

Abstract: Nascent polypeptides can induce ribosome stalling, regulating downstream genes. Stalling of ErmBL peptide translation in the presence of the macrolide antibiotic erythromycin leads to resistance in Streptococcus sanguis. To reveal this stalling mechanism we obtained 3.6-Å-resolution cryo-EM structures of ErmBL-stalled ribosomes with erythromycin. The nascent peptide adopts an unusual conformation with the C-terminal Asp10 side chain in a previously unseen rotated position. Together with molecular dynamics simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
156
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(165 citation statements)
references
References 75 publications
8
156
1
Order By: Relevance
“…Structurally, the extensive compaction and secondary structure formation of VemP results in an unprecedented total of 37 residues being housed within the upper two thirds (approximately 50–55 Å) of the ribosomal exit tunnel, which contrasts with the 21–33 aa that were visualized within the exit tunnel for other stalling peptides, such as SecM (Bhushan et al, 2011; Zhang et al, 2015), MifM (Sohmen et al, 2015), TnaC (Bischoff et al, 2014; Seidelt et al, 2009) and CMV (Bhushan et al, 2010b; Matheisl et al, 2015) (Figure 3). When calculating the theoretical minimal number of residues for the VemP peptide chain to stretch all the way from the PTC to the tunnel exit, it would require at least 51 aa, which is in stark contrast to only 31 aa for MifM and 34 for SecM due to lack of compaction.
10.7554/eLife.25642.010Figure 3.Comparison of the VemP nascent chain in the ribosomal tunnel with other stalling peptides.( a ) Overall superposition of VemP (model in green, surface in light green) with MifM (red, PDB ID 3J9W) (Sohmen et al, 2015), SecM (orange, PDB ID 3JBU) (Zhang et al, 2015), hCMV (yellow, PDB ID 5A8L) (Matheisl et al, 2015), TnaC (cyan, PDB ID 4UY8) (Bischoff et al, 2014) and ErmBL (blue, PDB ID 5JU8)(Arenz et al, 2016) in the ribosomal tunnel (light grey). The CCA-end of the P-tRNA is shown for reference.
…”
Section: Resultsmentioning
confidence: 99%
“…Structurally, the extensive compaction and secondary structure formation of VemP results in an unprecedented total of 37 residues being housed within the upper two thirds (approximately 50–55 Å) of the ribosomal exit tunnel, which contrasts with the 21–33 aa that were visualized within the exit tunnel for other stalling peptides, such as SecM (Bhushan et al, 2011; Zhang et al, 2015), MifM (Sohmen et al, 2015), TnaC (Bischoff et al, 2014; Seidelt et al, 2009) and CMV (Bhushan et al, 2010b; Matheisl et al, 2015) (Figure 3). When calculating the theoretical minimal number of residues for the VemP peptide chain to stretch all the way from the PTC to the tunnel exit, it would require at least 51 aa, which is in stark contrast to only 31 aa for MifM and 34 for SecM due to lack of compaction.
10.7554/eLife.25642.010Figure 3.Comparison of the VemP nascent chain in the ribosomal tunnel with other stalling peptides.( a ) Overall superposition of VemP (model in green, surface in light green) with MifM (red, PDB ID 3J9W) (Sohmen et al, 2015), SecM (orange, PDB ID 3JBU) (Zhang et al, 2015), hCMV (yellow, PDB ID 5A8L) (Matheisl et al, 2015), TnaC (cyan, PDB ID 4UY8) (Bischoff et al, 2014) and ErmBL (blue, PDB ID 5JU8)(Arenz et al, 2016) in the ribosomal tunnel (light grey). The CCA-end of the P-tRNA is shown for reference.
…”
Section: Resultsmentioning
confidence: 99%
“…The molecular- and atomic-level descriptions of macrolide-induced ribosome stalling have been elucidated in great detail (1217, 19, 58, 59, 7781); however, the relationship between ribosome stalling and the cellular levels of Erm methyltransferase (and thus bacterial resistance) has not been entirely consistent with clinical findings, wherein inducible constitutive resistance is commonly found in strains bearing ribosome-stalling-dead leader peptides. Our in vitro and in vivo analyses of the ErmBL EF nonsense mutants unequivocally demonstrate that increased mRNA stability could account for the observed ErmB overproduction, that distant macrolide relatives also promote the stabilization of the ermBL EF -ermB transcript, and that antibiotic exposure exerts a protective role on mRNA decay.…”
Section: Discussionmentioning
confidence: 99%
“…In the recently reported cryo-EM structure of 70S-ErmBL-RNC, the C-terminal region of the ErmBL NC was found to be well resolved, whereas tracing the remainder of the NC proved to be challenging for structural analysis, as the NC exhibited local flexibility (Figs. 3b and 5a;Arenz et al, 2014Arenz et al, , 2016. Previous studies suggested that erythromycin could induce translational arrest by binding to the antibiotic site and acting indirectly on the emerging ErmBL NC by redirecting its pathway along the exit tunnel (Arenz et al, 2014).…”
Section: Structural Analysis Of Ribosomebound Nascent Chainsmentioning
confidence: 99%
“…This region was modelled in using the N-terminal peptide sequence of ErmBL with and without the ERY molecule in an all-atom MD simulation. The graph from the MD simulation (bottom panel) shows the calculated rootmean-squared fluctuations (r.m.s.f.s) in the N-terminal residues (x axis) with (red) and without (green) the ERY antibiotic molecule (adopted from Arenz et al, 2016). (b) The schematic panel describes how co-translational folding of an Ig domain was studied using biochemical construct design, NMR spectroscopy and MD simulation.…”
Section: Structural Analysis Of Ribosomebound Nascent Chainsmentioning
confidence: 99%
See 1 more Smart Citation